Teaching mathematics remotely for the elementary level: Challenges and recommendations for development from the teacher’s viewpoint - Alrashdi, Thamer Nawaf (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the challenges in mathematics distance learning for the primary stage and recommendations for development through teachers view point. The study used the descriptive approach and the questionnaire as a tool for the study. The study sample consisted of (97) male and female mathematics teachers who involved in the primary stage in Al-Olayya Education Office at the Higher Education Department in the Riyadh Education Department. The results showed that there are great challenges in teaching mathematics remotely for the primary stage, and that the most important challenges are "some students depends on others in the login processes and completion of tasks in mathematics distance learning", "students frequently absent and ignore mathematics classes in distance learning, which affects their academic level”, “poor follow-up and feedbacks by families to their children in learning mathematics remotely”, "there is a great need to develop distance mathematics education for the primary stage, "one of the most suggested recommendations is “providing technical devices and a network Internet connection for those students who do not have it” and “reducing the educational content in the learning systems used to teach mathematics remotely, in terms of duties, activities, etc., and focusing on their quality, not their quantity.” "Headmasters, teachers, principals, and supervisors focus on learning outcomes through distance education." The study recommended establishing distance education centers in education departments, working on developing adaptive learning management systems, assigning supervision and management of distance education to specialists in the field of education technology. , Reducing administrative burdens on primary school mathematics teachers, activating the role of professional learning communities, working on adding a virtual mathematics laboratory, and providing continuous qualitative training for mathematics teachers.
Keywords: distance learning; teaching mathematics